Determining specialty pharmacy FTEs (full-time equivalents) needed in a clinical practice. (3rd September 2019) - Faucher, Kristina; Holton, Joseph; Favatella, Joseph; Capozzi, Donna; Demers, Richard
Abstract: Background: The Hospital of the University of Pennsylvania (HUP) created the Penn Specialty Pharmacy Program in 2014 to establish a pharmacy presence in clinics, with a patient focus on specialty medication access and adherence. The program utilizes both pharmacists and technicians to assist the clinics with medication counseling, prior authorizations, and copay assistance. As the program expands to more clinics throughout Penn, there is a growing need to employ more pharmacists and technicians, without a method in place to determine exactly how many FTEs are needed in clinic. Aims: To determine the number of clinical pharmacist and technician FTEs required in a clinical practice for maximum efficacy and patient care. Methods: Calculations were obtained by recording duties handled by the pharmacist (including those for which time does not allow), and determining if the task requires handling by a pharmacist, or if it could be delegated to a tech. This pilot program was first tested in the Dermatology Clinic at HUP, with the intent of launching throughout Penn, if successful. Once assignments were determined as either pharmacist or tech-appropriate, the recommended number of FTEs needed in the practice was calculated based on data obtained during an average 8-h work day: Duration of all tasks (in hours) × 5 days = ___ RPh/Tech Hours, and RPh/Tech Hours/40 = ___ RPh/Tech FTE. Results: The Dermatology pharmacist was observed over the course of 4 h as they completed several tasks, such as sending electronic rxs, patient calls, filling out paperwork for drug manufacturer programs, and responding to patient and provider cost-related concerns. Using the formula, and including roughly 7 h of assistance a pharmacist cannot currently provide (clinic/photopheresis rounds, appeals, etc.), this study was able to determine that the clinic would require ∼1.5 Pharmacist FTE and 0.39 Tech FTE. Conclusions: Many of the duties categorized as tech-specific were clerical or cost-related issues that did not require clinical intervention from a pharmacist. Addition of the 0.39 Tech FTEs would provide the RPh with additional resources to delegate duties to a tech, maximizing focus on patient care. This would also give the clinic an opportunity to include the pharmacist in other areas of the practice. More data may be needed to make a final decision on the needs of the clinic; however, this will be a helpful tool in validating departmental needs in other clinical settings for broad use in FTE determinations.